Crustal structure surrounding the northern Malawi rift and beneath the Rungwe Volcanic Province, East Africa. Issue 2 (9th August 2018) - Borrego, David; Nyblade, Andrew A; Accardo, Natalie J; Gaherty, James B; Ebinger, Cynthia J; Shillington, Donna J; Chindandali, Patrick RN; Mbogoni, Gabriel; Ferdinand, Richard Wambura; Mulibo, Gabriel; O'Donnell, JP; Kachingwe, Marsella; et al.
SUMMARY: The crustal structure surrounding the northern Malawi rift and beneath the Rungwe Volcanic Province (RVP) has been investigated using teleseismic earthquakes recorded on SEGMeNT broad-band seismic stations to determine the extent to which the crust has been modified by Cenozoic rifting and magmatism. The SEGMeNT network included 57 broad-band seismic stations deployed in northern Malawi and southern Tanzania between August 2013 and October 2015. Estimates of crustal thickness, shear wave velocity and Poisson's ratio have been obtained by modelling P -wave receiver functions using the H – k stacking method and jointly inverting receiver functions with Rayleigh wave phase velocities. These estimates are used to investigate the extent of magmatic modification to the crust, indicated by changes in Poisson's ratio, and the geometry of crustal thinning along the northern margins of the Malawi rift and beneath the RVP. The average crustal thickness for the four stations in the RVP is 39 km, the average Poisson's ratio is 0.28 ( Vp / Vs  = 1.83), and the average crustal shear wave velocity is 3.6 km s –1 . Although the RVP has been a site of ongoing magmatism since at least 17 Ma and is associated with a pronounced low velocity zone in the mantle, our results show little evidence that the bulk composition or thickness of the crust beneath the RVP has been significantly modified by magmatism or extension. However, Poisson's ratios of 0.29–0.31 ( Vp / Vs  = 1.85–1.91) at three of the stations in the RVP, where there is also no evidence for higher Vs, may indicate the presence of partial melt in the crust. The average crustal thickness of Proterozoic terranes surrounding the northern end of the Malawi rift ranges from 38 to 42 km. For most of the terranes, average Poisson's ratios are between 0.25 and 0.26 ( Vp / Vs  = 1.73–1.76), with the exception of the Irumide Belt, which has an average Poisson's ratio of 0.23 ( Vp / Vs  = 1.68). The average crustal shear wave velocities for all the terranes are either 3.6 or 3.7 km s –1 . These results indicate a bulk felsic to intermediate crustal composition for all terranes, consistent with previous results, and reveal that there is little, if any, crustal thinning beneath the uplifted flanks of asymmetric basins within the northern Malawi rift or beneath the RVP. Consequently, crustal thinning in the northern Malawi rift must be highly focused beneath the centres of rift basin segments, consistent with models of rift flank topography and gravity observations.